B fields in OB stars (BOB): The magnetic triple stellar system HD 164492C in the Trifid nebula - Gonzalez, Jorge Federico (2017)
HD 164492C is a spectroscopic triple stellar system that has beenrecently detected to possess a strong magnetic field. We have obtainedhigh-resolution spectroscopic and spectropolarimetric observations overa timespan of two years and derived physical, chemical, and magneticproperties for this object. The system is formed by an eccentric closespectroscopic binary (Ca1-Ca2) with a period of 12.5 days, and a massivetertiary Cb. We calculated the orbital parameters of the close pair,reconstructed the spectra of the three components, and determinedatmospheric parameters and chemical abundances by spectral synthesis.From spectropolarimetric observations, multi-epoch measurements of thelongitudinal magnetic fields were obtained. The magnetic field isstrongly variable on timescales of a few days, with a most probableperiod in the range of 1.4-1.6 days. Star Cb with Teff? 25 000 K is the apparently fastest rotator and the most massivestar of this triple system and has anomalous chemical abundances with amarked overabundance of helium, 0.35±0.04 by number. Weidentified this star as being responsible for the observed magneticfield, although the presence of magnetic fields in the components of theCa pair cannot be excluded. Star Ca1 with a temperature of about 24 000K presents a normal chemical pattern, while the least massive star Ca2is a mid-B type star (Teff ? 15 000 K) with anoverabundance of silicon. The obtained stellar parameters of the systemcomponents suggest a distance of 1.5 kpc and an age of 10-15 Myr.